The facilitators' perspective of interprofessional education at the Faculty of Health Sciences, University of the Free State - Cairncross, J. P. (University of the Free State, 2017)
Collaborative practice in healthcare occurs when various health workers with different areas of professional expertise work together with patients, their families and communities. The World Health Organisation (WHO) published a report that policy makers can apply to their own local context to address the local health needs and improve health outcomes through the implementation of interprofessional education programmes (IPE) that strengthen the health system. IPE can be defined as two or more professions learning “with, from and about each other” when they are brought together around a particular task. In 2014 the IPE programme was piloted at the Faculty of Health Sciences (FoHS), University of the Free State (UFS), and fourth year undergraduate students from the FoHS participated. Facilitators are staff from the different Schools of the FoHS, UFS, who assist small groups of undergraduate students to achieve the key outcomes/ competencies of the IPE programme. This study investigated the facilitators’ perspective, their opinions and attitudes, on the current and future IPE programmes at the FoHS, UFS. A quantitative cross-sectional study was designed by the researcher to investigate the facilitator’s perspective. The objectives of the study included determining the facilitator’s perspective on the current and future IPE programmes. Through the literature review the need for IPE and collaborative practice were identified. The facilitators’ perspective, students’ perspective and the delivery of an IPE programme were also identified. An online survey was emailed to all facilitators who had participated in the last IPE programme in 2015. The findings from the closed-ended questions were analysed and described. Findings from the open-ended questions were tabulated according to themes, categories and subcategories. All findings were discussed and summarised by the researcher. The study generated information on the facilitators’ perspective of the IPE programme that may be valuable in assisting programme coordinators in the development of future IPE programmes. Results indicated that not all facilitators were properly prepared for their role and the challenges they faced while conducting IPE sessions. Facilitators identified the need for additional training on the principles of IPE, conducting small group discussions and debriefing. Shortcomings of the current IPE programme, which do not allow for all students to actively participate with the specific case study, and a need to improve training of the standardised patients (SPs) were identified. Suggestions for future case studies were also made, i.e. to include the psychosocial aspects that can also affect the health of a patient. The study confirmed that key outcomes/ competencies of the IPE programme were being achieved. Facilitators were benefiting from the IPE programme not only by learning about the other healthcare professions but also in terms of their own personal growth and development. The study concludes with recommendations by the researcher to IPE programme coordinators. Undergraduate students should be better prepared regarding what is expected of them. Only facilitators who have completed a preparatory workshop should participate as a facilitator. The workshop should include the principles of IPE, facilitating small group discussions, conducting debriefing sessions and how to manage potential pitfalls that could arise during a session. SPs should be well informed regarding their role for the case study in order to deliver feedback to students. Case studies should be constructed to allow for active participation from all professions. Undergraduate psychology and social work students should be included in future IPE programmes to address the biopsychosocial model of health and illness.

Samewerkende praktykvoering vind plaas wanneer gesondheidsdienswerkers van verskillende gesondheidsberoepe gehaltediens lewer deur saam te werk tot voordeel van pasiënte, hul families en die gemeenskap. Die WGO het ŉ verslag gepubliseer wat beleidmakers op plaaslike vlak kan toepas wat die gesondheidsbehoeftes en die verbetering van gesondheidsorguitkomste aanspreek deur die implementering van ŉ interprofessionele onderwysprogram (IPO) wat die gesondheidsisteem versterk. IPO vind plaas as twee of meer beroepe “saam leer van en oor mekaar” wanneer hulle in ŉ spesifieke konteks en met ŉ bepaalde doel bymekaargebring word. Die Fakulteit Gesondheidswetenskappe (FG) aan die Universiteit van die Vrystaat (UV) het in 2014 die IPO program geloods waaraan vierdejaar voorgraadse studente deelgeneem het. Fasiliteerders is personeellede van die FG wat studente in klein groepe help om IPO doelwitte te bereik. Hierdie studie ondersoek die perspektief, menings en houdings van fasiliteerders in verband met die huidige en toekomstige IPO programme van die FG, UV. ŉ Kwantitatiewe kruissnitstudie is deur die navorser ontwerp om die fasiliteerder se perspektief te ondersoek. Die doelwitte van die studie sluit in die konseptualisering en kontekstualisering van IPO met behulp van ŉ literatuuroorsig, en om die fasiliteerder se perspektief op huidige en toekomstige IPO programme te bepaal. ’n Literatuuroorsig bevestig die behoefte aan IPO en samewerkende praktyk. Die fasiliteerder se perspektief, studente se perspektief en die aflewering van ŉ IPO program is ook ondersoek. ŉ Aanlynvraelys is aan alle fasiliteerders wat aan die IPO program in 2015 deelgeneem het, gestuur. Die bevindings van geslote antwoorde is ontleed en beskryf. Bevindings van die oop vrae is volgens tema, kategorie en subkategorieë getabelleer. Alle bevindings word bespreek en opgesom. Waardevolle inligting oor die fasiliteerder se perspektief op die IPO program het hieruit verskyn. Dit sal programkoördineerders van insig voorsien in die ontwikkeling van toekomstige IPO programme. Nie alle fasiliteerders was behoorlik voorbereid op hulle rol en op die uitdagings wat hulle ondervind het tydens die IPO sessies nie. Fasiliteerders het die behoefte aangedui vir verdere opleiding rakende die beginsels van IPO, die hou van kleingroepbesprekings, en ŉ behoefte aan ontlonting. Tekortkominge van die huidige IPO program, wat nie ruimte laat vir alle studente om aktief deel te neem aan die spesifieke gevallestudie nie, en ŉ behoefte daaraan om die opleiding van standaardpasiënte (SPs) te verbeter, is aangedui. Voorstelle vir toekomstige gevallestudies word ook gedoen, nl. om die psigososiale aspekte wat die gesondheid van ŉ student kan beïnvloed, ook in te sluit. Die studie bevestig vanuit die fasiliteerder se standpunt dat sleuteluitkomstes/ vaardighede van die IPO program tans bereik word deur die voorgraadse studente. Fasiliteerders trek ook voordeel uit die IPO programme omdat hulle sowel by die ander gesondheidsorgprofessies leer maar ook vorder ten opsigte van persoonlike groei en ontwikkeling. Die studie sluit af met aanbevelings aan IPO programkoördineerders vir die beplanning van toekomstige IPO programme. Voorgraadse studente moet beter voorberei word rakende wat van hulle verwag word. Slegs persone wat ŉ voorbereidende werkswinkel bygewoon het, behoort as fasiliteerders op te tree. Die werkswinkel moet insluit: beginsels van IPO, hoe om kleingroepbesprekings te fasiliteer, ŉ ontlontingsessie aan te bied en om moontlike vangplekke te bestuur. SPs moet goed ingelig word rakende hul rol vir die gevallestudie ten einde terugvoering aan studente te bied. Gevallestudies moet opgestel word om aktiewe deelname van alle professies in te sluit. Voorgraadse psigologie- en maatskaplike werkstudente behoort ingesluit te word by toekomstige IPO programme om die biopsigososiale model van gesondheid en siekte aan te spreek.
Keywords: Medical care -- Study and teaching; Medical education; Universities and colleges -- South Africa -- Bloemfontein; Community health services; Health care workers -- Training of; Dissertaton (M.HPE. (Health Professions Education)--University of the Free State, 2017